2016
DOI: 10.1098/rspb.2016.0068
|View full text |Cite
|
Sign up to set email alerts
|

A reduced propensity to cooperate under enhanced exploitation risk in a social mammal

Abstract: Conditional adjustment of cooperativeness to the expected pay-off might be a useful strategy to avoid being exploited in public good situations. Parental care provided towards all offspring in a communal nest (containing offspring of several females) resembles a public good. Females indiscriminately caring for all young share the costs equally, but the pay-off may vary depending on their contribution to the joint nest (number of own offspring). Females with fewer offspring in the joint nest will be exploited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…A communal litter in this study was determined when the second female gave birth within 16 days of the first female and pups were raised in a single nest (this definition has been used in other studies (Ferrari et al, 2016;König, 1994b)). Day 16 was chosen as weaning commences one day later when pups begin to eat solid food and reduce milk consumption (König and Markl, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A communal litter in this study was determined when the second female gave birth within 16 days of the first female and pups were raised in a single nest (this definition has been used in other studies (Ferrari et al, 2016;König, 1994b)). Day 16 was chosen as weaning commences one day later when pups begin to eat solid food and reduce milk consumption (König and Markl, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Within a communal litter, under our previous definition, litters can differ by up to 16 days in age (Ferrari et al, 2015;König, 1994b), and when heavily pregnant the female giving birth second in a communal litter may kill some or all of her partners young before giving birth herself (Ferrari et al, 2016;König, 1994b, such infanticide has never been observed after offspring reached 17 days of age).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, pairs of female house mice have been shown to adjust their contribution to communal care in response to unequal litter sizes, increasing the time spent caring for the group's offspring when their own offspring make up a larger fraction of the group (Ferrari et al. 2016). Similarly, soldier‐producing aphids increase their contributions toward gall defense behavior when in highly related groups, which comes at a cost to their personal reproduction (Abbot et al.…”
Section: Introductionmentioning
confidence: 99%